Feasibility analysis of loop colostomy closure in patients under local anesthesia - Abreu,Rone Antônio Alves de (2006)
PURPOSE: To verify prospectively the practicability of performing loop colostomy closure under local anesthesia and sedation. METHODS: In this study, 21 patients underwent this operation. Lidocaine 2% and bupivacaine 0.5% were utilized. Pain was evaluated during the operation, on the first postoperative day and at hospital discharge. Intraoperative events, postoperative complications and the acceptability of this procedure were analyzed. RESULTS: The mean duration of the operation was 133 minutes (range: 85 to 290 minutes). The mean postoperative hospitalization was four days (range: one to twelve days). No patients died. Complications occurred in two patients (9.4%): abdominal wall hematoma and operative wound infection. With regard to pain severity, scores of less than or equal to three were indicated in the intraoperative evaluation by 80% of the patients (17/21) and on the first postoperative day by 85% (18/21). At hospital discharge, 95.2% of the patients (20/21) said they were in favor of the local anesthesia technique. CONCLUSION: Loop colostomy closure under local anesthesia and sedation is feasible, safe and acceptable to patients.